In-Depth Assessment Practices among Intermediate School Social Studies Teachers and the Implications of Self-Efficacy in Light of Educational Modernization Standards - Miri Abdzaid Abdulhussein; Mohammed Tuama Kadhim Al Hamad (Environment and Social Psychology, 2026)
The current research aims at analysing self-efficacy and its relationship to in-depth assessment methods in light of educational modernization standards among intermediate school social studies teachers. The research objectives are: Creating a questionnaire measuring in-depth assessment methods, consisting of five domains. Determining the extent to which intermediate school social studies teachers possess self-efficacy, and identifying differences in self-efficacy among them according to gender (male-female). Determining the extent to which elementary school social studies teachers possess in-depth assessment methods in light of educational modernization standards, according to gender (male-female). Analyzing the statistical differences in the correlation between self-efficacy and in-depth assessment methods among social studies teachers, in light of educational modernization standards. The researcher relied on the use of the descriptive correlational approach to uncover self-efficacy, in-depth assessment methods, and the relationship between them, building a self-efficacy scale, which consists of (24) items distributed over three domains: activity testing, effort exerted, and perseverance in performing tasks, while ensuring the discriminatory power, internal consistency, and conditions of validity and reliability, and collecting information and data using the questionnaire tool, which consists of (42) items distributed over five domains, after completing the conditions of validity, reliability, and statistical analysis, and all its psychometric properties were confirmed. To further this, the researcher administered the scale and questionnaire to a sample of (300) male and female teachers for statistical analysis purposes, while the primary sample consisted of (120) intermediate school social studies teachers. The researcher relied on appropriate statistical methods for data analysis. After collecting and statistically processing the data using the Statistical Package for the Social Sciences (SPSS), the researcher arrived at a set of results upon which they formulated recommendations and suggestions.